Campylobacter spp. and Related Organisms in Poultry Pathogen-Host Interactions, Diagnosis and Epidemiology - Fonseca, Belchiolina Beatriz; Fernandez, Heriberto; Rossi, Daise Aparecida (Springer International Publishing : Imprint: Springer, 2016)
This book provides an extensive review of research into Campylobacter, Helicobacter and Arcobacter species found in poultry. It includes the epidemiology, diagnosis, immune response and disease control of these organisms in commercial poultry production. Antimicrobial resistance, and the incidence and human disease potential of these bacteria is also discussed. A global perspective is presented by experts from four continents - South America, North America, Europe and Africa. This reference work will be of value to the poultry industry, research laboratories, public health workers and students. An extensive overview of the relevant literature is provided by the reference lists at the end of each chapter.